Computational studies and structural insights for discovery of potential natural aromatase modulators for hormone-dependent breast cancer - Snehal Aditya Arvindekar; Sanket Rathod; Prafulla Balkrishna Choudhari; Pradnya Kiran Mane; Aditya Umesh Arvindekar; Suraj Narayan Mali; Bapu Thorat (BioImpacts)
Introduction: The aromatase enzyme plays an important role in the progress of hormone-dependent breast cancer, especially in estrogen receptor-positive (ER+) breast cancers. In case of postmenopausal women, the aromatization of androstenedione to estrone in adipose tissue is the most important source of estrogen. Generally 60%-75% of pre- and post-menopausal women suffer from estrogen-dependent breast cancer, and thus suppressing estrogen has been recognized to be a successful therapy. Hence, to limit the stimulation of estrogen, aromatase inhibitors (AIs) are used in the second-line treatment of breast cancer. Methods: The present computational study employed an in silico approach in the identification of natural actives targeting the aromatase enzyme from a structurally diverse set of natural products. Molecular docking, QSAR studies and pharmacophore modeling were carried out using the VLife Molecular Design Suite (version 4.6). The stability of the compounds was confirmed by molecular dynamics. Results: From molecular docking and analysis of interactions with the amino acid residues of the binding cavity, it was found that the amino acid residues interacting with the non-steroidal inhibitors exhibited π-stacking interactions with PHE134, PHE 221, and TRP 224, while the steroidal drug exemestane lacked π-stacking interactions. QSAR studies were performed using the flavonoid compounds, in order to identify the structural functionalities needed to improve the anti-breast cancer activity. Molecular dynamics of the screened hits confirmed the stability of compounds with the target in the binding cavity. Moreover, pharmacophore modelling presented the pharmacophoric features of the selected scaffolds for aromatase inhibitory activity. Conclusion: The results presented 23 hit compounds that can be developed as anti-breast cancer modulating agents in the near future. Additionally, anthraquinone compounds with minor structural modification can also serve to be potential aromatase inhibitors. The in silico protocol utilised can be useful in the drug discovery process for development of new leads from structurally diverse set of natural products that are comparable to the drugs used clinically in breast cancer therapy.